Synthetic stochastic ground motions compatible with the Chilean seismic hazard. (1st February 2021) - Loyola, L.; Rojas, F.; Ruiz, R.O.
Highlights: Optimization through Kriging metamodel for compatibility with GMPE. Tuned stochastic ground motion model of interplate and intraslab mechanism for Chile. Applicable for a range of periods from 0.1 to 3 seconds for rock soil conditions. Abstract: This paper develops a record-based stochastic ground motion model for the Chilean Subduction zone that generates ground motions compatible with the seismic hazard (represented by a local Ground Motion Predictive Equation GMPE) for both interplate and intraslab mechanism and considering rock soil conditions. The stochastic ground motion is obtained by the modulation of white-noise sequence in both time and spectral domain applying non-stationary filters. Compatibility is obtained by a proper tuning of predictive relationships, which offers a relation between seismological parameters and the driven parameters in the non-stationary filters. This process demands an intensive computational optimization problem where the parameters in the predictive relationships are found such that the stochastic ground motions generated match with the GMPE. The computational burden is decreased by the use of a Kriging metamodel which provides a high-fidelity approximation of the mean response spectra for different natural structural periods and the predictive relationship parameters. Once the predictive relationships are adjusted, the results are validated by comparing the prediction of mean spectral acceleration response from the GMPE with the prediction using the stochastic ground motion model. The Kriging model is built once and could be used to repeat the optimization for new GMPEs and predictive relationships (as a result of an updating process to incorporate new important seismic events) within a relatively low computational cost. In addition, a post-adjustment methodology is proposed to improve the results, using a scaling and spectral matching technique.